CULTURE, MYTH AND MEMORY: PERSPECTIVES ON THE RHETORICAL CONSTRUCTION OF THE ‘XENO’ IN GABRIEL GARCÍA MÁRQUEZ’S SHORT STORIES - Lewis, Anupa (PEOPLE: International Journal of Social Sciences, 2016)
The paper at hand is an attempt to lend perspective to the rhetorical construction of the ‘xeno’ in Gabriel García Márquez’s short stories. In this relation, the notion of the ‘xeno’ is discursively perused based on the application of diverse precepts by renowned theorists in logical progression: William Empson’s categories of ‘ambiguity’, Claude Levi Strauss’s concept of ‘bricolage’, Bakhtin’s premise of the ‘carnivalesque-grotesque’ contextualised by the principle of binary opposition, Viktor Shklovsky’s technique of ‘defamiliarization’, and Vladimir Propp’s impression of ‘archetypes’. In continuum, the trope of ‘ambiguity’ is identified as pivotal to the analysis.